2020
DOI: 10.1166/jctn.2020.8933
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things Based Video Surveillance Systems for Security Applications

Abstract: The principle point of this paper is to talk about the Video surveillance system plays major role in the security applications now a days. The need for surveillance systems are increasing drastically. Internet of things makes Video surveillance more effective. Internet of Things is an interrelated communication network for several systems and having the ability to transfer the information through the network without human or computer interaction. This paper reviews the network traffic due to Video surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Agama and Solikin [10] aimed to develop the Learning Media Video Tutorials for Engine Management System (EMS) practices in the Automotive engineering class and experts validity revealed that the tutorial video for diagnosing EMS on a vehicle is good and feasible to be implemented in the classroom activities. Ghosh et al [11] discussed the important role of video surveillance system in today's security applications.…”
Section: Introductionmentioning
confidence: 99%
“…Agama and Solikin [10] aimed to develop the Learning Media Video Tutorials for Engine Management System (EMS) practices in the Automotive engineering class and experts validity revealed that the tutorial video for diagnosing EMS on a vehicle is good and feasible to be implemented in the classroom activities. Ghosh et al [11] discussed the important role of video surveillance system in today's security applications.…”
Section: Introductionmentioning
confidence: 99%
“…• Ser authenticates 'S' built by MP • MP authenticates the Ser during the session with the session key On received uid, pwd, and bio from MP; α information is extracted from the smart card using Eqs. (11) and (12).…”
Section: Proposed Schemementioning
confidence: 99%
“…Together, all these factors have worked as a driving force for us to propose "A secure multi-factor authentication protocol for healthcare services using Cloud-based SDN". The Cloud-based SDN [10,11] combines the advantage of both SDN and Cloud offering a new revolution to the technological world in terms of efficiency and practicality. To ensure the confidentiality and privacy of patients' data, the proposed novel heterogeneous communication architecture provides a multifactor authentication policy.…”
Section: Introductionmentioning
confidence: 99%
“…This topic is extremely wide, and there are many areas that can be investigated in detail. In fact, it is possible to find several avenues of research from different points of view, such as [1] or [2], which provide an overview of the concept of surveillance systems.…”
Section: Introductionmentioning
confidence: 99%